2012
DOI: 10.1007/s12253-012-9590-0
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk and Low-Risk Human Papillomavirus in Esophageal Squamous Cell Carcinoma at Mazandaran, Northern Iran

Abstract: Cancers are the second most common cause of non-accidental deaths in Iran, following cardiovascular deaths. Mazandaran, near the Caspian Littoral at north of Iran have identified as a several-high incidence area for Esophageal Squamous Cell Carcinoma (ESCC) in the world. Several associated risk factors, such as dietary and cultural habits, infectious agents, nutritional deficiencies, too much use of tobacco and alcohol and infection to certain DNA tumor viruses (HPVs), including environmental and genetic facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
3
13
1
Order By: Relevance
“…The most frequent infecting HPV type in patients with CRC was HPV-18 in keeping with previous studies (Lee et al, 2001;Motlagh et al, 2007;Giuliani et al, 2008). Furthermore, we detected HPV-45 and HPV-31, which have not been previously reported in patients with colorectal carcinoma in Iran but have been recognized as high-risk types in malignant diseases (Yahyapour et al, 2013). In comparison with this study, Damin et al (2007), Chen et al (2012) and Burnett-Hartman et al (2013) found HPV-16 as the most frequently detected HPV type in patients with CRC.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The most frequent infecting HPV type in patients with CRC was HPV-18 in keeping with previous studies (Lee et al, 2001;Motlagh et al, 2007;Giuliani et al, 2008). Furthermore, we detected HPV-45 and HPV-31, which have not been previously reported in patients with colorectal carcinoma in Iran but have been recognized as high-risk types in malignant diseases (Yahyapour et al, 2013). In comparison with this study, Damin et al (2007), Chen et al (2012) and Burnett-Hartman et al (2013) found HPV-16 as the most frequently detected HPV type in patients with CRC.…”
Section: Discussionsupporting
confidence: 51%
“…Currently,types 16,18,31,33,35,39,45,51,52,56,58, as low-risk types; and types 26, 53 and 66 considered as probably oncogenic (Burnett-Hartman et al, 2008;Yahyapour et al, 2013). The oncogenic potential of HPV is related to its ability to interfere, upon viral integration into the host cell DNA, with the cell cycle and tumor supportive function of the p53 and pRB proteins (Giuliani et al, 2008).…”
Section: Research Articlementioning
confidence: 99%
“…In other study on same samples, positive specimens were evaluated by Real-time PCR to determine HPV genotypes. From the 49 HPV positive cases, of ESCC patients, 5 (23.1%), 11 (55 %) and 9 (56.3%) of upper, middle and lower third of ESCC specimens, respectively were positive by at least one high and one low-risk HPV genotypes (Yahyapour et al, 2012). In the same study in Iran in 2012, the prevalence of highrisk human papillomavirus Types 16 and 18 in cervical samples from healthy women with normal Pap smears was tested by polymerase chain reaction.…”
Section: Discussionmentioning
confidence: 99%
“…More than 30% of cancers may be prevented with healthy life cycles and/ or immunization against infections of cancer factors (Human Papilloma Virus HPV and Hepatitis B-Virus HBV). Also, 30% of these cases can be cured in the case of premature diagnosis [5]. Among cancers, esophageal cancer is crucially important.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the report of Globocan 2008, the Age Standardized Incidence Rate (ASR) in developed countries has been reported to be 1.2 in females and 6.5 among males and this rate is 10.1 for males and 4.2 for females in the world. According to the latest statistics from the National Cancer Registration Center, with Age Standardized Rate (ASR) of 5.88 among females this rate is ranked in the fifth position while ASR of 6.15 among males is placed at the eighth position [5,11]. Esophageal cancer has remarkable discrepancies in Iran in such a way that after gastric and skin cancers in the Ardabil province, this cancer is ranked as the second most popular cancer after gastric cancer among females [12].Most northern and northwestern areas in Iran are at high risk of esophagus and gastric cancer, while the central and western provinces are at medium risk and the southern regions are at a low risk [13].…”
Section: Introductionmentioning
confidence: 99%